2021
DOI: 10.3390/su13116294
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internal Control in Firms’ Coping with the Impact of the COVID-19 Pandemic: Evidence from China

Abstract: Internal control plays a role in risk prevention for firms when dealing with serious emergencies, which ensures the sustainable development of firms during a crisis. Based on the rapid outbreak of COVID-19 in China, this paper empirically tests whether internal control alleviates the negative impact of the pandemic on firm performance. Using a sample of Chinese listed firms from the first quarter of 2019 to the third quarter of 2020 and employing the difference-in-difference (DID) method, we find that the firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…According to dynamic capability theory, when the uncertainty of the external environment increases, internal control can form good power checks, balances, and coordination mechanisms within the company, which improve the ability of firms to cope with crises and have stronger resistance during crises and higher recovery after crises. Our results are similar to Zhu and Song (2021) [9] and Hao and Zhang (2022) [47]; however, Zhu and Song (2021) emphasized the impact of internal controls on firms' financial performance, while this paper examines the value of internal controls in a crisis from an enterprise resilience perspective [9]. Hao and Zhang (2022)'s study concluded that internal control could reduce corporate risk and improve enterprise resilience in normal times [47].…”
Section: Conclusion and Future Prospects 61 Conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to dynamic capability theory, when the uncertainty of the external environment increases, internal control can form good power checks, balances, and coordination mechanisms within the company, which improve the ability of firms to cope with crises and have stronger resistance during crises and higher recovery after crises. Our results are similar to Zhu and Song (2021) [9] and Hao and Zhang (2022) [47]; however, Zhu and Song (2021) emphasized the impact of internal controls on firms' financial performance, while this paper examines the value of internal controls in a crisis from an enterprise resilience perspective [9]. Hao and Zhang (2022)'s study concluded that internal control could reduce corporate risk and improve enterprise resilience in normal times [47].…”
Section: Conclusion and Future Prospects 61 Conclusionsupporting
confidence: 93%
“…However, relatively few studies have been conducted on the role of internal control during crises. Only Zhu and Song (2021) studied the role of internal control in firms' response to the impact of COVID-19 and concluded that internal control could mitigate the negative impact of the epidemic on firms' performance; the higher the quality of firms' internal control, the better the firm's financial performance in the epidemic journals [9]. Rikhardsson et al (2021) used the 2008 financial crisis to study the banking industry and found that internal control systems are the key to effective crisis response [10].…”
Section: Introductionmentioning
confidence: 99%
“…The main dependent variable is ROA, our proxy for firm performance. Referring to relevant research, firm performance can be mainly measured by financial performance and market performance, and financial performance more reliably reflects the real operating situation of the firm [57]. In this paper, we intend to measure the firm performance from the financial performance aspect.…”
Section: Measurement Of Firm Performancementioning
confidence: 99%
“…This test is mainly to distinguish between companies' efforts to promote the employment of people with disabilities and other CSR behaviors. As discussed above, many studies have focused on the firm performance implications of CSR activities, while most studies have confirmed that CSR will have a significant positive impact on firm performance [43][44][45][46]57,59]. Corporate social responsibility activities will produce a reputation effect [43,44] and improve the relationship with other stakeholders such as government and consumers [47,48], which is often related to higher financial performance.…”
Section: Considering Other Csr Behaviormentioning
confidence: 99%
“…The government should objectively evaluate the degree of low carbon economic development of enterprises, with a view to formulating corresponding standard incentives and punishment measures for them. Based on this, it is very important to establish a sound, reasonable and feasible low-carbon operation management indicator system (Zhu and Song, 2021). Through reasonable selection of indicators, comprehensively evaluate the information related to low-carbon operation of SMEs, and correctly measure the degree of low-carbon operation of enterprises.…”
Section: Introductionmentioning
confidence: 99%